Students' Perceptions of the Future of Devin AI: A Case Study at IPB University - Hardika, Bagus; Valencia, Cindy; Adzani, Rivanka Marsha; Barus, Irma Rasita Gloria; Fami, Amata (Fakultas Sains dan Teknologi UIN Imam Bonjol Padang, 2024)
Devin AI is an autonomous artificial intelligence assistant referred to as an